2006
DOI: 10.1590/s0100-204x2006000900005
|View full text |Cite
|
Sign up to set email alerts
|

Híbridos de tomateiro longa-vida com frutos de maior intensidade de coloração

Abstract: Resumo − O objetivo deste trabalho foi avaliar a viabilidade do emprego simultâneo de genes mutantes de amadurecimento e de coloração, nos locos nor A , rin, og c e hp, em híbridos de tomateiro, com diferentes backgrounds e combinações genotípicas. O experimento foi conduzido em estufas, em delineamento de blocos ao acaso, com 20 genótipos e três repetições. Houve tendência dos mutantes de amadurecimento (nor + /nor A e rin + /rin) para reduzir a produção precoce de frutos, mas não a produção total. Genótipos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
(1 reference statement)
1
6
0
1
Order By: Relevance
“…Similar effects on fruit color were found by Faria et al (2003) and Cá et al (2006). In fact, the three smallest chromaticity angles (nearest to red) among the studied genotypes were TEX-435 of the genotype og c+ /og c rin + /rin, and TEX-437 and TEX-440 of the genotype og c /og c rin + /rin nor + /nor A .…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Similar effects on fruit color were found by Faria et al (2003) and Cá et al (2006). In fact, the three smallest chromaticity angles (nearest to red) among the studied genotypes were TEX-435 of the genotype og c+ /og c rin + /rin, and TEX-437 and TEX-440 of the genotype og c /og c rin + /rin nor + /nor A .…”
Section: Resultssupporting
confidence: 88%
“…Araújo et al (2002) have shown that the alcobaça allele in homozygosity (nor A /nor A ) prolongs the postharvest shelf life by the reduction of weight loss and the increase of firmness, and reduces the lycopene and beta-carotene concentrations, besides increasing the Brix/acidity ratio, mainly in association with the genotypes hp/hp and hp + /hp or with og c /og c ; however, its external color limits its commercial use. Cá et al (2006) in the evaluation of the viability of simultaneous use of mutant genes, for maturity and for color in tomato hybrids, in the loci nor A , rin, og c , or hp, found that these genotypes exhibited better post-harvest shelf life than the normal genotypes, and concluded that the genotypic constitutions nor + /nor A og c+ /og c , together with nor + /nor A og c+ /og c hp + /hp, were considered most promising, both for improving postharvest conservation and for maintaining or improving the internal color of tomato fruit. Faria et al (2006) showed that the use of the mutants og c or hp, in heterozygosity, improves the color and increases the concentrations of beta-carotene and lycopene of fruit in rin + /rin and rin + /rin nor + /nor A long shelf life hybrids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutant alleles that may act markedly on the postharvest shelf life of fruits are "alcobaça" (nor A ), "ripening inhibitor" (rin) and "non ripening" (nor) (Andrade Junior et al, 2005;Kim et al, 2013;Garg et al, 2014). The color mutant alleles "high pigment" (hp) and "old gold crimson" (og c ) are responsible for increasing the production of carotenoids, especially lycopene, in the fruit, improving the nutritional quality, and can be used together with ripening mutant alleles within the same genotype, allowing simultaneous improvements on both postharvest shelf life and nutritional quality of fruit (Andrade Junior et al, 2005;Cá et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the use of ripening mutants, the allele rin (ripening inhibitor) is the most used allele in modern cultivars (Cá et al, 2006). These alleles delay ripening and prolong shelf life, interfering mainly on the firmness and carotenoid pigments synthesis, in addition to being useful for a better understanding of the processes which regulate the maturation and the development of new cultivars with longer shelf life (Dias et al, 2003;Faria et al, 2006;Cá et al, 2006).…”
Section: Introductionmentioning
confidence: 99%